Comparative evaluation of the remineralizing efficacy of calcium sodium phosphosilicate agent and fluoride based on quantitative and qualitative analysis - Saranya Mony; Arathi Rao; Ramya Shenoy; Baranya Srikrishna Suprabha (Wolters Kluwer Medknow Publications, 2015)
Background: Calcium sodium phosphosilicate (NovaMin) is an agent that is claimed to release calcium and phosphate ions intraorally to help the self-repair process of enamel. It is used extensively as a desensitizing agent, but the chemical reactions that occur may promote apatite formation enhancing remineralization. The present study was undertaken to evaluate the ability of NovaMin to remineralize an experimentally induced demineralized lesion. The evaluation was done based on the quantitative and qualitative analysis of enamel over the period of 15 and 30 days. Materials and Methods: A sample of 120 noncarious premolar teeth extracted for orthodontic reasons were used for the study. Baseline data for hardness, Ca/PO 4 , and surface characteristics before and after demineralization process was obtained. All the teeth were brushed twice daily at 12 h interval with the test agents using a powered toothbrush for 2 min. The samples were tested on the 15 th and 30 th day. Results: Calcium phosphate ratio and hardness in both the groups improved during the study period. Fluoride group showed higher values for Ca/PO 4 and hardness but was not statistically significant with the P > 0.05. Scanning electron microscope pictures showed that the deposition of the material over the decalcified enamel is more smoother and uniform with NovaMin and more irregular with fluoride. Relevance: NovaMin is found to be as effective in improving the Ca/PO 4 ratio and hardness in a demineralized enamel as fluoride. Hence, it can be a new alternate material for remineralization of enamel with less toxic effects compared to fluorides.